The role of health and advocacy organisations in assisting female sex workers to gain access to health care in South Africa - Nosipho Faith Makhakhe; Anna Meyer-Weitz; Helen Struthers; James McIntyre (BMC, 2019)
Abstract Background Globally, female sex workers (FSWs) are considered a key population group due to the high HIV prevalence. Studies show that there are various factors in some contexts that render FSWs marginalised, which limits their access to sexual reproductive health (SRH) services. Access to SRH services are particularly challenging in countries where sex work is criminalised such as is the case in South Africa. Evidently, there are alternative ways in which FSWs in this context receive non-stigmatising SRH care through non-governmental organisations. The aim of this study was to understand the functioning of these non-governmental health care services as well as to document the experiences of FSWs utilising these services. Methods Eleven focus group discussions were held with 91 FSWs. In addition, 21 in-depth individual interviews with researchers, stakeholders and FSWs were conducted. Interview guides were utilised for data collection. Informed consent was obtained from all participants. Data were analysed thematically. Results The FSWs expressed challenges related to SRH care access at public health facilities. The majority felt that they could not consult for SRH-related services because of stigma. The non-governmental health and advocacy organisations providing SRH services to FSWs through their mobile facilities utilising the peer approach, have done so in a way that promotes trust between FSWs and mobile health care providers. FSWs have access to tailored services, prevention materials as well as health information. This has resulted in the normalising of HIV testing as well as SRH seeking behaviours. Conclusion This study has established that health and advocacy organisations have attempted to fill the gap in responding to SRH care needs of FSWs amidst intersecting vulnerabilities. FSWs' engagement with these organisations has encouraged their willingness to test for HIV. However, it is important to note that these organisations operate in urban areas, thus FSWs operating outside these areas are most likely exposed to compounding health risks and lack access to tailored services.